Poly(lactic acid) scaffolds modified by gelatin for the controlled release of tetrandrine in vitro - Zhang Ye (Functional Materials, 2017)
To mimic natural extracellular matrix architecture, tetrandrine-loaded poly(L-lactic acid) scaffolds modified by gelatin were prepared via phase separation, solvent replacement and freeze-drying. The purpose of this work was to combine the biological effects of tetrandrine and the advantages of poly(L-lactic acid) scaffolds which was modified by gelatin to enhancing the mass transfer features of controlled release systems. Tetrandrine contained in the scaffolds was confirmed by X-ray photoelectron spectroscopy (XPS) and Fourier-transform infrared (FT-IR) spectroscopy. Tetrandrine did not change the morphous, crystallinity and thermodynamics of the scaffolds which demonstrated by differential scanning calorimetry (DSC), scanning electron microscopy (SEM) and X-ray powder diffractometry (XRD). The results of this study showed a sustained release with 79.15% for 188 days in vitro.